Factors connected to axillary colonization by resistant organisms of intensive care unit patients - Arcanjo, Rafaela; Oliveira, Adriana (Journal of Health Care, 2017)
Introduction: The spread of bacterial resistance is almost always linked to colonized or infected patients. The detection of patients colonized allows timely implementation of interventions to prevent transmission of resistant organisms and consequently infection. Objective: To analyze incidence colonization by resistant microorganism (MR) in the axillary region and possible risk factors in patients admitted to an Intensive Care Unit (ICU). Materials and methods: It is about a historical cohort study conducted between august 2013 and august 2015, involving 837 patients. The data were collected from the medical records of patients and results of microbiological tests. Results and conclusions: Among the patients studied, 122 (14.6%) were colonized by MR, especially: Enterobacter sp. 25%, Acinetobacter baumannii 20%, Staphylococcus aureus 15%, Pseudomonas aeruginosa 12%. The factors associated with colonization by resistant microorganisms were: length of stay in ICU ? 9 (OR = 32.4), use of invasive procedure (OR = 25.7) and the use of antimicrobial (OR = 13.9). The relationship between colonization by MR and risk factors shows the need for monitoring and protocol institution aimed at accession to the control measures of the spread of these microorganisms.
Keywords: Control Infections; Microbial Drug Resistance; Patient Safety; Intensive Care Unit; Antimicrobial Susceptibility